IFN-β is a potent inhibitor of insulin and insulin like growth factor stimulated proliferation and migration in human pancreatic cancer cells - Booy, Stephanie (Am J Cancer Res, 2015)
Introduction: Pancreatic cancer is a highly aggressive malignancy with few treatment options. The overexpression of several growth factors, including insulin and insulin-like growth factors (IGFs), can underlie the aggressive nature of this disease. Previous research has demonstrated potent effects of interferon (IFN)-β on pancreatic cancer cell growth, however up till now it is unknown whether IFN-β is able to counteract IGF1, IGF2 and insulin-induced pancreatic cancer cell proliferation and migration. Methods: Expression of IGF- and insulin receptors was determined and the stimulatory effects of IGF1, IGF2 and insulin on cell proliferation and migration, as well as the inhibitory effects of IFN-β were evaluated in 3 human pancreatic adenocarcinoma cell lines. Results: Both the insulin- and the IGF1 receptor were variably expressed in the cell lines. IGF1, IGF2 and insulin were capable of stimulating cell proliferation in all three cell lines, however cell migration was significantly enhanced only in the BxPC-3 cell line. IFN-β significantly inhibited IGF1-, IGF2- and insulin-stimulated proliferation in all three cell lines in a dose and time dependent manner. Furthermore, in the BxPC-3 cell line IFN-β significantly inhibited both basal and IGF1-, IGF2- and insulin-stimulated cell migration. Conclusion: Both IGF1, -2 and insulin were capable of stimulating proliferation and migration in human pancreatic cancer cells irrespective of the type of receptor expressed. This study demonstrates that insulin, in addition to IGF1 and IGF2, may play an important role in the progression of pancreatic cancer. Moreover, IFN-β strongly inhibits growth factor stimulated cell proliferation and migration. Our study supports previous findings which have suggested that IFN-β can be a potential promising anti-cancer agent in pancreatic cancer.